Investigative journalism and whistleblowers: the ethical handling of sources in the “Inkathagate” and “Vlakplaas” newspaper exposes’ - Raghunath, Mahendra (My University, 2017)
Journalists are often presented with leaked information from whistleblowers. Having the information and writing the story, as well as handling a source that may or may not want to be anonymous, gives rise to ethical dilemmas on the part of the journalist. This was certainly true for journalists reporting on the political violence in South Africa during the late 1980s and the early 1990s. Journalists operate under codes of practice that are set by various media organisations and must ensure that in using whistleblower information to write their stories, “they must avoid breaches of ethics, fairness, factual accuracy and contextual accuracy” (Houston, B. et al., 2002: 538). And most importantly, journalists are ethically bound to protect their sources. This research looks at the interaction between journalists and their sources of information in two major stories that involved the use of whistleblowers. It discusses and compares the issue of “source handling”, in the following two South African stories which used information leaked by whistleblowers: a. the 1991 “Inkathagate” story, which was broken by the Weekly Mail newspaper; b. “Vlakplaas” hit squad story, initially involving the Weekly Mail (20 October 1989) and then Vrye Weekblad (November 1989). This study also brings into focus the issue of strengthening journalistic ethics in the South African context. It contends that the “Inkathagate” and “Vlakplaas” stories were dependent on the verification of the information, as well as the ethical handling of the whistleblowers. This study raises questions about the motivations of the whistleblowers, their relationships with the journalists, as well as the critical role of the public’s “right to know”, or “public interest”.
A research report submitted in partial fulfilment of the requirements for the degree of the University of Witwatersrand’s Masters by Coursework and Research Report in Journalism studies, Johannesburg, February 2017
Keywords: Journalistic ethics--South Africa; Journalism--South Africa; Investigative reporting--South Africa